2022
DOI: 10.1128/mbio.03060-21
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying the Cellular Entry and Host Range Restriction of Lujo Virus

Abstract: Lujo virus (LUJV) infects humans with high mortality rates, but the host range of LUJV remains unknown. We found that rodent-derived cell lines were less susceptible to LUJV infection than were human-derived cell lines, and the differential susceptibilities were determined by the difference of CD63, the intercellular receptor of LUJV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Mopeia virus (MOPV) is also found in this rodent throughout Mozambique and Zimbabwe, but has not been shown to cause human disease [ 12 , 13 , 14 ]. LUJV caused a small outbreak of Lujo hemorrhagic fever (LHF) in 2008 in Zambia and South Africa ( Figure 2 ); the natural host of LUJV is still unknown [ 15 , 16 , 17 ]. The NW arenaviruses are distributed throughout the South and North American continents and are further divided phylogenetically into four clades: Clade A, B, C, and A/Rec (D) ( Figure 1 and Figure 2 ).…”
Section: Classification and Distribution Of Arenavirusesmentioning
confidence: 99%
“…Mopeia virus (MOPV) is also found in this rodent throughout Mozambique and Zimbabwe, but has not been shown to cause human disease [ 12 , 13 , 14 ]. LUJV caused a small outbreak of Lujo hemorrhagic fever (LHF) in 2008 in Zambia and South Africa ( Figure 2 ); the natural host of LUJV is still unknown [ 15 , 16 , 17 ]. The NW arenaviruses are distributed throughout the South and North American continents and are further divided phylogenetically into four clades: Clade A, B, C, and A/Rec (D) ( Figure 1 and Figure 2 ).…”
Section: Classification and Distribution Of Arenavirusesmentioning
confidence: 99%
“…Many of these family viruses include multiple agents associated with acute gastroenteritis or febrile illnesses that can cause severe diseases in humans. Lassa virus (LASV) ( Zhu et al., 2021b ), Lymphocytic choriomeningitis virus (LCMV), Tacaribe, Machupo, Junin ( Huang et al., 2017 ), Guanarinto, Sabia, and the recently discovered White-Water Arroyo ( Guo et al., 2013 ) and Lujo viruses ( Saito et al., 2021 ) are high-impact pathogens belonging to the Arenaviridae family. HanVs infect a wide range of mammalian hosts; Hanta, Seoul, Puumala, and Sin nombre viruses are etiological agents of hemorrhagic fever with renal syndrome and hantavirus cardiopulmonary syndrome in humans ( Wu et al., 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…CD63, a tetraspanin residing in intracellular vesicles including endosomes and lysosomes, promotes LUJV GP-mediated membrane fusion (Raaben et al, 2017). Recent studies have shown that CD63 is an important factor in determining the host range of LUJV (Saito et al, 2021).…”
Section: Introductionmentioning
confidence: 99%